Impact of a Five Minute Counseling Session of Proper Inhaler Technique on Control of Asthma in Patients Presenting to Tertiary Care Hospital - Rashid Iqbal, Khawar Shoaib, Hassan Farooq, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the effectiveness of counseling session of inhaler technique in improving control of symptoms in asthma patients, the factors affecting the improper inhaler technique and association of inhaler use with control of asthma. It has been observed that patients coming to tertiary care hospitals have poor asthma control and patients does not know exactly how to use inhaler in asthma symptoms. Study design: A facility based Observational, Prospective, Cross-sectional study conducted on patient with asthma symptoms and signs. Settings: This study was done in Department of Medicine, Sir Ganga Ram hospital Lahore. Timings: From 24-1-2023 to 23-5-2023. Methods: A facility based Observational, Prospective, Cross-sectional study was conducted on patient with asthma symptoms and signs. This study described the improvement in asthma symptoms by counseling sessions of using inhaler techniques in asthma patients. This study was done in Department of Medicine, Sir Ganga Ram hospital, Lahore. Patients who come to Out patient department of the hospital were selected who had asthma symptoms and signs. Sample size: A total of eighty Patients were selected with asthma symptoms and signs. Patients history were recorded and they were asked to use inhaler and there inhaler use technique were scored. Sample Selection: Inclusion Criteria: Patients age 16 years above, Both male and female patients, new onset asthma symptoms and signs, previously uncontrolled asthma on corticosteroid inhalers and meter dose inhaler devices. Exclusion criteria: Patients with history of chronic bronchitis and Patient with history of emphysema, Patients age less than 16 years. Data Collection procedure: A questionnaire was given to doctors who filled the data and record of patients with asthma symptoms and signs. A proper five minutes counseling of inhaler technique was done in asthma patients who came to Out Patient department of hospital. A questionnaire was filled and used for interpretation of results. We separated patients in two groups. One group of patients did not know how to use inhaler and other group knew how to use inhalers. Improper technique for use of inhaler defined as less than 75 percent of corrected steps done for use of inhaler device. Then we scored patient about the level of effective use of inhaler in asthma patients. We did a five minute counseling session to teach them how to use inhalers properly. We followed these patients in out patients department of tertiary care of hospital and see the improvement in control of asthma symptoms. We observed that patients asthma were controlled, if symptoms and signs improved, reduce nocturnal awakening of patients with cough and shortness of breath, improved quality of life and daily activities. We did the comparison of both group of patients coming to tertiary care hospital and see the impact of five minute counseling of proper inhaler techniques in improving asthma control in these patients. Results: A total of eighty patients were enrolled in the study. Mean age of Patients were 38.12 years and among them 40 percent were male 60 percent were female. 85.12 percent patients asthma symptoms were not controlled, 14.17 percent patients asthma symptoms were controlled. 11 percent patients were diabetics, 26 percent patients had hypertension, 11 percents were smokers, 3.7 percent patients had ischemic heart disease. Among total 80 patients, 48.12 percent patients were using inhalers. 70 percent patients did not know how to use inhaler devices correctly , 30 percent knew how to use inhalers. All patients who were well controlled with asthma were those who knew how to use asthma inhaler correctly. After counseling of proper inhaler techniques, patients were followed and questionnaire were interpreted and inhaler technique was scored, 78 percent patients have better control of asthma symptoms who scored well on use of inhaler technique of asthma devices. Practical Implication: Patients asthma are well controlled, if patients know there technique to use inhaler properly and if patients are well compliant to their inhaler medications for asthma. Conclusion: Patients who were counseled about proper use of inhaler techniques in asthma patients have better asthma symptoms control as compare to patients who did not know how to use asthma inhaler devices. These findings emphasis the need for patient education about asthma inhaler use for good control of asthma symptoms. Keywords: Asthma, Inhaler Technique, Allergens, Control of symptoms.